CLINICAL PROFILE OF PATIENTS WITH HYPOSPADIAS IN SAIFUL ANWAR GENERAL HOSPITAL, MALANG - Henrizal, Fenni; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2025)
Objective: This study aims to present the clinical profile of hypospadias patients in the Urology Department of Saiful Anwar Hospital. Material & Methods: This retrospective study analysed the characteristics of delayed hypospadias cases at Saiful Anwar General Hospital in Malang. The study utilized a descriptive design with a quantitative approach, conducted from January 2019 to February 2024. All patients with hypospadias who visited were included in this study. Data were presented in percentage format to illustrate the distribution of cases. Results: Among the 250 patients, 242 (97%) were classified as having a delayed diagnosis. Of all the cases, 141 (56%) were located in Malang. Proximal hypospadias was the most prevalent anomaly, affecting 131 (52%) of the patients. Additionally, there were 88 cases (35% of the total) of mid-shaft hypospadias and 31 cases (13% of the total) of distal hypospadias. Out of the total, 39 patients (16%) had undescended testis (UDT), while 53 patients (22%) had bifid scrotum as an additional condition. Of the 46 patients, 18.4% experienced preterm labor, and approximately 78% of the newborns, specifically 194 of them, had a birth weight over 2500 grams. The healthcare provider participated in 226 out of 232 births, accounting for 97% of the total. The condition was primarily diagnosed by obstetricians, who identified 42% of cases, while midwives identified 58% of the cases. Conclusion: Most hypospadias patients presenting at Saiful Anwar Hospital are diagnosed late, with proximal hypospadias being the most prevalent type. Accompanying conditions include bifid scrotum, occurring in 22%, and undescended testes, present in 16% of cases. This finding presents a potential opportunity to enhance the standard of care. Keywords: Hypospadias, UDT, bifid scrotum.